Physiology of fishes - Evans, David H.; Claiborne, James B.; Currie, Suzanne (Boca Raton : CRC Press, 2014)
Following the success of the bestselling third edition, this newly updated and completely revised fourth edition of The Physiology of Fishes provides comprehensive coverage of the most important aspects of the form and function of fishes. It covers the most recent advances as well as fundamental subjects such as cardiovascular physiology, intestinal transport, and gill ion uptake. Written by an international group of experts, this book contains fresh approaches, with completely new treatment of the original topics and the addition of new chapters
Index 443-453p.
Keywords: Chemoreception; Pain perception; Thermal stress; Cardiac regeneration